Diagnosis of Extrapulmonary Legionellosis in Allogeneic Hematopoietic Cell Transplant Recipients by Direct 16S Ribosomal Ribonucleic Acid Sequencing and Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry. (13th July 2017) - Franco-Garcia, Alexandra; Varughese, Tilly A; Lee, Yeon Joo; Papanicolaou, Genovefa; Rosenblum, Marc K; Hollmann, Travis J; Koehne, Guenther; Boulad, Farid; Babady, N Esther; Tang, Yi-Wei; Seo, Susan K
Abstract: Identifying extrapulmonary legionellosis is difficult due to the lack of clinical suspicion and limitations of conventional microbiologic methods. We present a case series of hematopoietic cell transplant recipients with extrapulmonary legionellosis diagnosed via molecular diagnostics: 16S ribosomal ribonucleic acid gene Sanger sequencing and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry.